The pie that Molly grew - Heavenrich, Sue (Sleeping Bear Press, 2023)
Using "The House That Jack Built" rhyme scheme, a young girl plants a seed and follows its journey from sprout to vine to the final fruit which she then uses to bake a pie. Includes information on pumpkins and a pumpkin pie recipe.